Complementing Graphenes: 1D Interplanar Charge Transport in Polymeric Graphitic Carbon Nitrides. (6th November 2015) - Merschjann, Christoph; Tschierlei, Stefanie; Tyborski, Tobias; Kailasam, Kamalakannan; Orthmann, Steven; Hollmann, Dirk; Schedel‐Niedrig, Thomas; Thomas, Arne; Lochbrunner, Stefan
Abstract : Charge transport in polymeric graphitic carbon nitrides is shown to proceed via diffusive hopping of electron and hole polarons with reasonably high mobilities >10 −5 cm 2 V −1 s −1 . The power‐law behavior of the ultrafast luminescence decay exhibits that the predominant transport direction is perpendicular to the graphitic polymer sheets, thus complementing 2D materials like graphene.